LEKSIKON SAMIN SEBAGAI CERMIN PANDANGAN DUNIA PENUTURNYA - Suhandan Suhandan (LITERA, 2015)
AbstractThe Samin people are a group of Javanese speakers. However, the Javanese they useis a little different from the common Javanese in some ways. For example, they use somedistinctive lexicons such as rukunan ‘husband/wife’, pondhokan ‘house’, turun ‘child’, and soon. This article discusses the distinctive lexicons in the Samin community to explain whythey use such unique lexicons. The discussion employs the framework of anthropologicallinguistics studying linguistic facts in a broad sociocultural context. The findings reveal thatthe use of distinctive lexicons by the Samin community is not coincidental, but related totheir perspectives on viewing things labeled by the lexicons; how they do so is influencedby the Saminism ideology. In addition, it is also revealed that in some instances, for theSamin community, the lexicons are not just labels that mark something, but also tools tointerpret something.